Cholecalciferol Additively Reduces Serum Parathyroid Hormone and Increases Vitamin D and Cathelicidin Levels in Paricalcitol-Treated Secondary Hyperparathyroid Hemodialysis Patients - Zheng, Jing-Quan (Nutrients, 2016)
Background: Active Vitamin D analogues are used clinically for prevention and treatment of secondary hyperparathyroidism (SHPT) in hemodialysis (HD) patients. Nutritional vitamin D supplementation is used for additional local parathyroid (PTH) suppression, with lower incidence of hypercalcemia and hyperphosphatemia. This study evaluates the possible beneficial effects of combined vitamin D treatment (paricalcitol and cholecalciferol). Methods: Sixty HD patients with serum parathyroid hormone (iPTH) >300 pg/mL were enrolled. All patients administered 2 mcg/day of paricalcitol and were randomly allocated into control group (placebo) or study group (cholecalciferol) for 16 weeks. Serum 25(OH)D(3), iPTH and human cathelicidin (hCAP-18) were measured at baseline and during follow-up. Results: iPTH levels decreased in the study group appropriately and were more significantly decreased at 16 weeks. Study group had significantly increased 25(OH)D(3) levels. In addition, the study group had significantly increased serum hCAP-18 levels compared with control group. Correlation analysis showed a significant correlation between the percentage increase in serum hCAP-18 and 25(OH)D(3) levels. Conclusions: Cholecalciferol, in combination with paricalcitol, additively lowers the iPTH levels in a significant number of patients after 16 weeks of supplementation. A dose of 5000 IU/week of cholecalciferol could maintain serum 25(OH)D(3) levels above 30 ng/dL as early as 8 weeks after beginning supplementation. Doubling of serum cathelicidin levels were noted after 16 weeks of cholecalciferol supplementation in 40% of study patients.